ANALISIS FAKTOR YANG MEMPENGARUHI KEPATUHAN IMPLEMENTASI CARA DISTRIBUSI OBAT YANG BAIK (CDOB) PADA PEDAGANG BESAR FARMASI DI KOTA CIREBON: ANALYSIS OF FACTORS AFFECTING COMPLIANCE WITH GOOD DRUG DISTRIBUTION PRACTICES (GDDP) IN PHARMACEUTICAL WHOLESALERS IN CIREBON CITY - Yunika Yunika; Dwi Yuliani; Nur Setyaningsih (Program Studi Farmasi-Fakultas Matematika dan Ilmu Pengetahuan Alam-Universitas Tulang Bawang, 2026)
Abstract Pharmaceutical wholesalers (PBF) play a strategic role in the drug distribution chain, ensuring the safety, quality, and authenticity of medicines circulating in society. Compliance with Good Drug Distribution Practices (GDDP) is a legal obligation regulated by the Head of BPOM Regulation. This study aims to analyze the factors influencing GDDP implementation compliance among pharmaceutical wholesalers in Cirebon City. An observational analytic method with a cross-sectional approach was employed using a structured questionnaire distributed to 52 respondents from 12 PBF in Cirebon City. Variables studied included human resources, facilities and infrastructure, documentation systems, management commitment, and regulatory oversight. Data were analyzed using Chi-Square test (α = 0.05) followed by logistic regression for multivariate analysis. The results indicate that all variables had a significant relationship with GDDP compliance (p < 0.05). Human resource competency was identified as the most dominant factor. This study recommends strengthening continuous training for PBF personnel and increasing the intensity of regulatory supervision to improve GDDP compliance. Keywords: GDDP, Compliance, Pharmaceutical Wholesaler, Drug Distribution, Cirebon City